2014
DOI: 10.1007/s10444-014-9361-4
|View full text |Cite
|
Sign up to set email alerts
|

On the convergence of regular families of cardinal interpolators

Abstract: In this note a general way to develop a cardinal interpolant for l 2 -data on the integer lattice Z n is shown. Further, a parameter is introduced which allows one to recover the original Paley-Weiner function from which the data came.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 10 publications
1
33
0
Order By: Relevance
“…We need a definition similar to the one found in [8]. For our purposes, we make the following definition.…”
Section: Definitionmentioning
confidence: 99%
See 4 more Smart Citations
“…We need a definition similar to the one found in [8]. For our purposes, we make the following definition.…”
Section: Definitionmentioning
confidence: 99%
“…Additionally, in the language of Aldroubi and Unser, all of these examples are more or less interpolating generating functions for L 2 ([−π, π]), see Section 4.3 in [2] for more details. The work done in [8] for the space L 2 suggested that an appropriate generalization to L p should exist.…”
Section: Examplesmentioning
confidence: 99%
See 3 more Smart Citations